Re: Full simplify problem

*To*: mathgroup at smc.vnet.net*Subject*: [mg122282] Re: Full simplify problem*From*: dimitris <dimmechan at yahoo.com>*Date*: Sun, 23 Oct 2011 06:24:44 -0400 (EDT)*Delivered-to*: l-mathgroup@mail-archive0.wolfram.com*References*: <j7u59t$u$1@smc.vnet.net>

On Oct 22, 1:18 pm, "A. Lapraitis" <ffcita... at gmail.com> wrote: > Hello, > > Could anyone explain why the following does not give zero? > > In[72]:= Assuming[ > x == y + z, > FullSimplify[ > E^x - E^(y + z) > ] > ] > > Out[72]= E^x - E^(y + z) > > Thanks! Actually private communication with Andrzej Kozlowski made me understand that the approach in my second message was incorrect. For example each of the following evaluate to True In[116]:= Assuming[x === y + z, FullSimplify[E^x - E^(y + z) === 0]] During evaluation of In[116]:= $Assumptions::fas: Warning: One or more assumptions evaluated to False. >> Out[116]= True In[119]:= Assuming[x === y + z, FullSimplify[E^x - E^(y + z) < 0]] During evaluation of In[119]:= $Assumptions::fas: Warning: One or more assumptions evaluated to False. >> Out[119]= True In[120]:= Assuming[x === y + z, FullSimplify[E^x - E^(y + z) > 0]] During evaluation of In[120]:= $Assumptions::fas: Warning: One or more assumptions evaluated to False. >> Out[120]= True Assuming False every predicate becomes True. Of course the approach in the first message is correct. Dimitris

**Follow-Ups**:**Re: Full simplify problem***From:*DrMajorBob <btreat1@austin.rr.com>